Effect of thiophene, furan moieties and zinc ions on melamine-based porous polyaminals properties and catalytic activity on CO2 cycloaddition reaction. (15th August 2022) - Sobarzo, Patricio A.; Tundidor, Alain; Sanz-Perez, Eloy S.; Terraza, Claudio A.; Maya, Eva M.
Graphical abstract: Highlights: Melamine based polyaminals (PAs) with thiophene or furan moieties within the network are reported. Thiophene based PAs showed higher aminals content and CO2 uptake than furan-based. Zinc complexes were prepared from the thiophene based PAs with higher CO2 uptake. ZnPAs catalyze the conversion of CO2 under milder conditions than melamine-PAs reported. Thiophene size plays a favourable role in the access of reactants to aminals and zinc ions. Abstract: A new series of melamine-based porous polyaminals containing thiophene or furan moieties of different size in the polymer network were prepared and fully characterized. The new polyaminals were N-rich polymers with nitrogen content between 10 and 28%, exhibited micro-, meso- or macroporosity, depending on the type and size of the thiophene or furan moiety with specific surface areas in the range of 23–490 m 2 /g. The CO2 uptakes were moderated, between 1 and 5% and those polyaminals with higher CO2 uptake capacity were selected as catalysts to promote the conversion of CO2 into cyclic carbonate and also to prepare the corresponding zinc complexes, which were used as catalysts in the same reaction. The selected catalysts showed good catalytic performance working under much milder reaction conditions (CO2 pressure of 4 bar, 80 °C, 0.1 mol % of cocatalyst) than the examples of melamine-based polyaminals published so far for this reaction.